Critical Financial Education in the interdisciplinary context in Science and Mathematics studies - Marinho, Fabio Cardoso; Pinto , Gisela Maria da Fonseca (Educação Matemática Debate, 2024)
The aim of this study is to present a theoretical essay that integrates Mathematics Education, Financial Education and Critical Environmental Education to weave together, in an interdisciplinary way, strategies that give students access to fundamental skills, with a view to a healthy relationship between consumption, dealing with finances, decision-making and socio-environmental and socio-economic issues. From the studies presented, it was possible to highlight the relationship between environmental impacts, the lifestyle of the citizen-consumer and Critical Education, signaling healthy options for learning to take place more effectively, with possibilities for better harmony between individuals and the environment, through practical actions to build a more balanced society.